The dentition of Manidens condorensis (Ornithischia; Heterodontosauridae) from the Jurassic Can˜ado´n Asfalto Formation of Patagonia: morphology, heterodonty and the use of statistical methods for identifying isolated teeth - Becerra, Marcos Gabriel (2013)
The recently described Manidens condorensis is one of the most completely known taxa of the family Heterodontosauridae from the southern landmasses. However, some dental aspects are not well known due to preservational problems in the type material. This contribution reports new isolated teeth found in the Cañadón Asfalto Formation (Early-Middle Jurassic). These teeth are referred to Manidens condorensis based on the presence of autapomorphic characters of the unusual dentition of this taxon, such as the highly asymmetric tooth crowns and small crenulations on each denticles. The isolated crowns are well preserved and reveal the presence of undescribed and new autapomorphical features, including apical and basal wear facets on the occlusal surface of isolated crowns and a wear surface also in the caniniform tooth. We carried out statistical analyses (including morphogeometrical and discriminant analyses), using the holotype crowns as a morphological starting point, for characterising shape variation of the crowns along the toothrow and for identifying the position of isolated crowns. These analyses allow defining morphological regions within the postcaniniform toothrow and produce a metrically based discriminant function to predict the hypothetical position of future discoveries, providing a methodological framework that could be applied to other extinct heterodont dinosaurs.